Geographical variation in a fatal outcome of acute myocardial infarction and association with contact to a general practitioner. (November 2016) - Ersbøll, Annette Kjær; Kjærulff, Thora Majlund; Bihrmann, Kristine; Schipperijn, Jasper; Gislason, Gunnar; Larsen, Mogens Lytken
Abstract: Background: Geographical variation in incidence and mortality of acute myocardial infarction (AMI) is present in Denmark. We aimed at examining the association between contact to a general practitioner (GP) the year before AMI and a fatal outcome of AMI. Methods: Register-based data and individual-level addresses including 69, 608 individuals with AMI in 2006-2011. A Bayesian hierarchical logistic regression model was used to examine the association. Results: A fatal outcome of AMI was seen among 12.0% (78%) of individuals with (without) contact to a GP the year before AMI. A significant association was estimated. Conclusions: A fatal outcome of AMI was significantly associated with contact to a GP. A high population to GP ratio and long distance to GP could not explain the increased odds of a fatal outcome of AMI for individuals with no contact to a GP.